Machine learning and simulation of GPR data - Tan, Jia Dian (Nanyang Technological University, 2022)
Ground penetrating radar (GPR) is a geophysical inspection method that makes use of electromagnetic waves to detect objects underneath a surface. In this project, a center frequency GPR as well as a dual polarizing GPR were used to carry out underground tree root detection by obtaining image scans, mainly in the form of b-scans. Currently, there are limitations to the number and nature of b-scans that can be obtained from experimentation. Not many ground truth b-scans of tree roots are readily available from the GPRs that the team is using. As such, a machine learning approach to image generation was explored to generate b-scans that can reproduce realistic and novel representations of these scans. In this paper, the deep learning domain of Generative Adversarial Network (GAN) will be explored and implemented to achieve the generation of the b-scans. Drawbacks and improvements to the model will also be explored, such as using other variants of GANs through Deep Convolutional GANs and Wasserstein GANs. Other uses of GANs will also be explored to complement the generation of realistic b-scans. One such usage will be the image translation capability of GANs to add realistic features to ground truth b-scans to obtain the desired b-scans for this project.